LED flashlight technology facilitates wild meat extraction across the tropics. Issue 9 (29th July 2020) - Bowler, Mark; Beirne, Christopher; Tobler, Mathias W; Anderson, Matt; DiPaola, Anna; Fa, John E; Gilmore, Michael P; Lemos, Lisley P; Mayor, Pedro; Meier, Amelia; Menie, Guillaume Menie; Meza, Diana; et al.
Abstract : Hunting for wild meat in the tropics provides subsistence and income for millions of people. Methods have remained relatively unchanged since the introduction of shotguns and battery‐powered incandescent flashlights, but the short battery life of such flashlights has limited nocturnal hunting. However, hunters in many countries throughout the tropics have recently begun to switch to brighter and more efficient light‐emitting diode (LED) flashlights. Such brighter spotlights stimulate the freeze response of many species, and improved battery life allows hunters to pursue game more often and for longer periods of time. Interviews with hunters in African and South American tropical forests revealed that LEDs increase the frequency and efficiency of nocturnal hunting, and subsequently the number of kills made. In Brazil, these findings were supported by harvest data. The marked change in efficiency brought about by LEDs, well known to hunters around the world, poses a major threat to wildlife. Here we consider the implications of the increasing use of LED lights in hunting for communities, governments, wildlife managers, and conservationists.